First 100 farm words with a lift-the-flap matching game - Karabatzia, Villie (London Pat-a-Cake, 2021)
this big book introduces essentail frist farm words to curious little oncs.with questions to answer, a matching flap game and lots to spot and count, it is perfect for busy toddlers
Linguistic notions
with a lift-the-flap matching game
For children aged 3 - 6 years
Keywords: Linguistic notions